SHARIA GLOBAL TRADE AND SUSTAINABLE DEVELOPMENT GOALS: A LITERATURE REVIEW ON THE PRINCIPLES OF JUSTICE AND BUSINESS ETHICS - Adhim, Abdullah Jimly Hasanal (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the relationship between Sharia principles in global trade and sustainable development goals. The primary focus of this study is the application of the principles of justice and business ethics in the global Sharia-compliant trading system. Although the principle of economic justice within the Sharia-compliant system has been discussed previously, no study has specifically linked it to sustainable development goals in the context of global trade. Through a literature review, this study explores how Sharia principles, such as justice in resource distribution and transparency in transactions, can support the achievement of the Sustainable Development Goals (SDGs). Furthermore, this study also identifies the challenges and opportunities inherent in integrating Sharia principles with sustainable development goals in global trade. This study provides new insights into the potential of Sharia-compliant global trade to support a more just and sustainable economy.